Integration of The Lean Six Sigma Model in The Distribution of Goods to Minimize Delivery Delays at PT. AMA - Arman Maulana Akbar; Efta Dhartikasari Priyana; Yanuar Pandu Negoro (Journal of Development Research, 2023)
PT. AMA is a company operating in the goods distribution industry (cement-non-cement). A problem that is the focus of research at PT. AMA is a delay in delivery by the company's fleet. In this research, the method used is the integration of the Lean Six Sigma model which combines the philosophy of waste reduction from Lean and the high-level quality control approach from Six Sigma where with the help of research using Visual Stream Mapping to visualize the company's operational processes to identify in more depth the root of the problems that cause there is a delay in the delivery of goods. Which results in a total lead time of 770 minutes and value-added time of 420 minutes with an error rate of 22% and a Six Sigma value of 2.29. Proposed improvements to the new goods distribution operational system using the 5W-1H method analysis. The results of the research that has been carried out show that the integration of the Lean Six Sigma model significantly reduces waste, optimizes a distribution process and increases on-time delivery.